Private Sector Development And Economic Diversification: Evidence From Nigeria - Ogbonna, Innocent Chukwuka (Advances in Social Sciences Research Journal, 2018)
Nigerian economy is monolithic with primary commodity oil export constituting above 95 per cent of total export receipts since the 1990s. This feature has its implications on the economy as the vagaries associated with oil export are transmitted directly to the economy. Recently, economists argue in favour of economic diversification, that is, one with expanded varieties of determinants of income and employment, as key to erecting a sustainable growth and development. In fact, economic diversity and economic development are linked since the former provides opportunities for income growth, employment and development which a mono-product economy lacks. Notwithstanding attempts towards attaining a more diversified economy, this has not translated into commensurate employment, infrastructural provision and sustained advancement in the standard of living due to limited market assess, unskilled labour, insecurity, corruption, etc. This study seeks to examine empirically the relationship between private sector development and economic diversification from 1999Q1-2016Q4. Employing time series analysis with data drawn from Nigeria, the results indicate that the level of private sector investment is a significant determinant of economic diversification both in the short- and long-run. Equivalently, quality of infrastructure, violent conflicts, quality of governance, and openness are also important determinants of economic diversification in the short- and long-run.